APLIKASI ARTIFICIAL INTELLIGENCE (AI) DALAM PROSES ADMINISTRATIF PEMERINTAHAN: ASPEK HUKUM DAN REGULASI - Loso Judijanto (CV. Adiba Aisha Amira, 2025)
The application of Artificial Intelligence (AI) in government administrative processes can improve the efficiency and effectiveness of public services by processing data quickly and accurately, as well as helping to personalise services to the community. Nevertheless, the use of AI in government faces significant challenges in the legal and regulatory fields, particularly in ensuring the transparency and accountability of AI systems to avoid bias and discrimination. Legal aspects that must be considered include personal data protection and cybersecurity, as large-scale data processing increases the risk to individual privacy. Therefore, comprehensive regulations are needed to ensure that AI is applied responsibly and ethically, protecting public rights and interests while still encouraging innovation in government administration.